Nomenclatural notes in Neotropical Acanthocinini (Coleoptera, Cerambycidae) - Monné, Miguel A.; Machado, Vanessa S. (Zootaxa, 2009)
During the study of the Neotropical Acanthocinini (Coleoptera, Cerambycidae, Lamiinae) a series of papers that describes the diverse cerambycid beetle fauna of the Americas has been produced (e.g. Monné, 1982, 1985, 1998). To help to stabilize the nomenclature for this tribe, we propose several changes concerning the genera Hylettus Bates, 1864 and Nyssodrysternum Gilmour, 1960.